Approximative characteristics of the isotropic classes of periodic functions of many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
Exact-order estimates are obtained for the best orthogonal trigonometric approximations of the Besov (B_p,θ^r) and Nukol’skii (H_p^r ) classes of periodic functions of many variables in the metric of L_q , 1 ≤ p, q ≤ ∞. We also establish the orders of the best approximations of functions from the same classes in the spaces L_1 and L_∞ by trigonometric polynomials with the corresponding spectrum.